(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
Undergraduate management students in Nepalese higher education institutions often face challenges in balancing academic engagement with their overall learning experience, which can influence their satisfaction with teaching quality. This study examines the relationship between academic engagement and students’ satisfaction with teaching quality, focusing specifically on teachers’ planning, instructional delivery methods, and communication skills. A cross-sectional survey research design was employed, and data were collected using a self-administered questionnaire from a sample of two hundred and fifty (N=250) management students enroled in higher education institutions across Nepal. Descriptive statistical techniques were used to analyse the data and identify patterns of academic engagement and satisfaction with teaching quality. The findings indicate that students generally demonstrate moderate to high levels of academic engagement and report a strong level of satisfaction with teaching quality. The results further reveal a positive association between academic engagement and teaching satisfaction, suggesting that more engaged students tend to perceive teaching practices more favourably and benefit more effectively from instructional processes. The study highlights important implications for higher education institutions, emphasising the need to strengthen student engagement through interactive teaching strategies, supportive learning environments, and inclusive academic practices. It further suggests that institutional policies should promote equitable opportunities for engagement across all student groups, ensuring inclusivity regardless of gender or background, to enhance overall teaching effectiveness and student learning outcomes.